Interferon Lambda 4 Genotype Is Not Associated with Recurrence of Oral or Genital Herpes - Lang Kuhs, Krystle A.; Kuniholm, Mark H.; Pfeiffer, Ruth M.; Chen, Sabrina; Desai, Seema; Edlin, Brian R.; Peters, Marion G.; Plankey, Michael; Sharp, Gerald B.; Strickler, Howard D.; Villacres, Maria C.; Quinn, Thomas C.; et al. (PLOS ONE, 2015)
IFNL4-ΔG/TT (rs368234815) genotype is associated with hepatitis C virus clearance and may play a role in other infections. IFN-λ4 protein is generated only in individuals who carry the IFNL4-ΔG allele. The IFNL4 rs12979860-T allele, which is in strong linkage disequilibrium with IFNL4-ΔG, was recently reported to be associated with more frequent and severe oral herpes episodes. We investigated the association of IFNL4-ΔG/TT with herpes simplex virus (HSV)-related outcomes among 2,192 African American and European American participants in the Women’s Interagency HIV Study (WIHS). WIHS is a prospective cohort study of human immunodeficiency virus (HIV)–infected and at-risk women that began in 1994. This report includes follow-up through 2013. Available data included: HSV–1 and HSV–2 antibodies at study entry; bi-annually ascertained episodes of (self-reported) oral herpes, (self-reported) genital sores and (clinician-observed) genital ulcers; HSV–2 DNA in cervicovaginal lavage (CVL) specimens. IFNL4-ΔG/TT genotyping was determined by TaqMan. We compared women with IFNL4-ΔG/ΔG or IFNL4-TT/ΔG genotypes (i.e., IFNL4-ΔG carriers) to those with the IFNL4-TT/TT genotype, adjusting for age, race and HIV status. For outcomes with repeated measurements, the adjusted odds ratio (aOR), 95% confidence interval [CI] and p-value were determined using a generalized estimating equations approach. Median participant age at enrollment was 36 years; 81% were African American, 74% were HIV-infected. Among 1,431 participants tested for antibodies, 72.8% were positive for HSV–1 and 79.0% were positive for HSV–2. We observed no association between IFNL4-ΔG/TT genotype and any outcome: HSV–1 or HSV–2 antibody prevalence (p>0.1, all comparisons); oral herpes (aOR, 1.2; p = 0.35); genital sores (aOR, 1.0; p = 0.71); genital ulcers (aOR, 1.1; p = 0.53); detectable HSV–2 DNA in CVL (N = 322; aOR, 0.71; p = 0.49); HSV–2 DNA level (p = 0.68). In this large prospective study, IFNL4-ΔG/TT genotype was not associated with HSV-related outcomes, including episodes of oral or genital herpes.